Scope and search: understanding FPS players’ information seeking behavior - Quiroga, David Carlos O.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
In the study, the researcher sought to understand and analyze the information seeking behavior displayed by first-person shooter (EPS) players. Specifically, the researcher sought to understand what information needs players have before and after playing the game and what the methods they employ to satisfy their information needs. It was initially theorized that this behavior will be similar to the findings of Adams (2009) in a previous study. To answer this, a focus group discussion was held with FPS players to discover their perceived informational needs and the ways they go about seeking this information. The findings from the focus group discussion were used to construct and framework describing the information seeking behavior of FPS players. It was concluded that players develop information needs after playing and their primary methods of seeking information are online sources that they interact with in their everyday lives.
Thesis
Keywords: Information behavior; Video gamers; Computer games -- Social aspects